Desired Impact of an ERP Implementation on the Quality of Information - Jabłoński, Artur; Kawczyńska, Marta; Pietrzak, Żaneta; Wnuk-Pel, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
This paper aims to present the expectations of the employees of the company in which the study has been conducted in terms of the impact of an ERP system implementation on the quality of information, in particular the information generated by the system of management accounting. To achieve the research objective, the authors conducted a case study using a questionnaire. The survey was conducted in a company which was implementing an ERP system. The results allow to conclude that the expectations of its employees in relation to the improvement of the quality of information were high. In particular, they desired an improvement in terms of speed of obtaining information and an increase in its accuracy. The respondents felt that the implemented system would be significantly useful in their work, mainly by supporting its most important aspects and improving control.